2002
DOI: 10.1021/bi020486r
|View full text |Cite
|
Sign up to set email alerts
|

A Heterodimerizing Leucine Zipper Coiled Coil System for Examining the Specificity of a Position Interactions:  Amino Acids I, V, L, N, A, and K

Abstract: We use a heterodimerizing leucine zipper system to examine the contribution of the interhelical a-a' interaction to dimer stability for six amino acids (A, V, L, I, K, and N). Circular dichroism (CD) spectroscopy monitored the thermal denaturation of 36 heterodimers that generate six homotypic and 30 heterotypic a-a' interactions. Isoleucine (I-I) is the most stable homotypic a-a' interaction, being 9.2 kcal/mol per dimer more stable than the A-A interaction and 4.0 kcal/mol per dimer more stable than either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
168
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(176 citation statements)
references
References 44 publications
7
168
0
1
Order By: Relevance
“…This limited set of rules has allowed considerable progress in the areas of coiled-coil prediction and design (1, 3), but our findings suggest that additional advances will be possible based on a more sophisticated treatment. Previously elucidated factors include lateral pairing of nonpolar side chains (9-16), which is driven by stereochemical complementarity, and lateral pairing of polar side chains (9)(10)(11)(12)(13)(14)(15)(16)33), which is driven by hydrogen bonding (at least for Asn-Asn pairs). In addition, pairing preferences are influenced by the electrostatic interactions (attractive or repulsive) between ionized side chains (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This limited set of rules has allowed considerable progress in the areas of coiled-coil prediction and design (1, 3), but our findings suggest that additional advances will be possible based on a more sophisticated treatment. Previously elucidated factors include lateral pairing of nonpolar side chains (9-16), which is driven by stereochemical complementarity, and lateral pairing of polar side chains (9)(10)(11)(12)(13)(14)(15)(16)33), which is driven by hydrogen bonding (at least for Asn-Asn pairs). In addition, pairing preferences are influenced by the electrostatic interactions (attractive or repulsive) between ionized side chains (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive work by Vinson et al, for example, has shown that the contribution of a given buried a side chain to parallel coiled-coil dimer stability depends on the identity of the lateral hydrophobic packing partner (a-aЈ interaction) (9,12). We have recently shown that lateral partners (a-dЈ) influence antiparallel coiled-coil stability (20).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Given the reports from the GCN4 coiled-coil, a yeast leucine zipper protein [20][21][22] , the hydrophilic core residues, N231, could be a weakness of the core packing stability. Other structure features are the lack of inter-subunit polar interaction that stabilizes the assembly [23][24][25] ( Supplementary Fig. S2b) and the dual-conformation of Cys residues in the core, suggesting a possibility of switching of the disulfide bonding in response to redox ( Supplementary Fig.…”
Section: Coiled-coil Assembly Domain Of Mhv1/vsop and Its Structurementioning
confidence: 99%
“…Additionally, the Tyr and Gln residues of the SKYQ motif occupy the g and a positions, respectively, in the Leu zipper after this last Leu. The a, e, and g positions in the helix of Leu zippers determine the specificity of dimerization between Leu zippers (Acharya et al, 2002;Deppmann et al, 2004). Additionally, the presence of a positively charged amino acid in the a position of one of the heptads-Lys in ig1, ial1, Sbig1, Osig1, and AS2 and Arg in ial2, ial3, and Osial1-suggests that these proteins do not homodimerize.…”
Section: Fine Mapping and Cloning Of Ig1mentioning
confidence: 99%